Pengaruh Analisis Faktor Muat Trans Pakuan Bogor Koridor Terminal Bubulak-Cidangiang Terhadap Keseimbangan Supply and Demand - Prahardian, Novandi; Susilo, Hartanto (Zenit, 2012)
With a total area of 111.73 km and a population that continues to grow every year, the city of Bogor in need of adequate transportation facilities to meet the need for public transportation. In this case, the integrity of the science of transportation are necessary to achieve a balance of supply and demand. Therefore, it need for additional supply in the form of transportation facilities of Trans Pakuan Bogor to meet the needs of the surrounding community. Trans Pakuan Bogor is a kind of Bus Rapid Transit which operate in Bogor City. Since 2007, Trans Pakuan had operated and during the operation range of time there are a lot of obstacle in it. 4th years since Trans Pakuan operated, occupant quantity, service quality and operation,it’s possible to change. Therefore, this examination is done to detect effectiveness from Trans Pakuan Bogor in corridor Terminal Bubulak-Cidangiang with load factor as the indicator. This examination aim  determines load factor values and analyzed route characteristics of Trans Pakuan Bogor based on  load factor values change, especially for corridor Terminal Bubulak-Cidangiang. Beside be first corridor and longtime operate, this corridor is the scope from this examination. Based on analyzed result, route characteristics of Trans Pakuan has same trend  for Terminal Bubulak-Cidangiang direction, at the morning peak hour and also at afternoon peak hour. But this matter not applicable for direction on contrary, that is Cidangiang-Terminal Bubulak direction, the route characteristics has different trend between morning peak hour and afternoon peak hour.  Keywords: Bus Rapid Transit, load factor, Trans Pakuan, Supply and Demand.